Dietary effects of hydroponic wheat sprouted fodder on growth performance of turkey - Ali, Hussein Suleiman; Miah, Abdul Gaffar; Sabuz, Sabbir Hossain; Asaduzzaman, Mohammad; Salma, Ummay (Research in Agriculture Livestock and Fisheries, 2019)
The study was conducted at Faculty of Veterinary and Animal Science, Hajee Mohammad Danesh Science and Technology University (HSTU), Dinajpur, Bangladesh to determine the nutritional composition and economic value of hydroponic wheat sprouted fodder (HWSF) replaced by commercial concentrate feed (CCF) and it’s effect on growth performance of turkey. A total of 75 poults were selected and randomly assigned into five groups (T1, T2, T3, T4 and T5), each group with 3 replications having 15 birds in each. T1 considered as control group and fed only CCF, where T2, T3, T4 and T5 groups fed 95, 90, 85 and 80% CCF along with 5, 10, 15 and 20% HWSF, respectively. The amount of DM, CP and NFE were significantly higher (P<0.01) in hydroponic maize sprouted fodder than hydroponic wheat and sesbania sprouted fodder where Ash, OM, CF, DM and EE were not significant. Live weight of turkey was increased in T1 (2074.86 g), T2 (2130.4 g), T3 (2125.75 g) and T4 (2085.53 g) except T5 (1959.4 g) groups. The live weight gain was almost similar in the turkey of T2 (29.55 g/d), T3 (29.26 g/d), T4 (28.44 g/d) and T1 (27.69 g/d) groups except T5 (23.85 g/d) group. The lowest but best feed efficiency was observed in T2 (2.60) group. Cost benefit analysis showed higher benefit in T2, T3 and T4 than in T1 and T5 group. Therefore, the overall results revealed that dietary supplementation of HWSF up to 15% may improve live weight, feed efficiency of turkey as well as reduce total feed cost. Res. Agric., Livest. Fish.6(1): 101-110, April 2019